2022
DOI: 10.1155/2022/7617258
|View full text |Cite
|
Sign up to set email alerts
|

The Compatibility of Alisma and Atractylodes Affects the Biological Behaviours of VSMCs by Inhibiting the miR-128-5p/p21 Gene

Abstract: Objective. The compatibility of Alisma and Atractylodes (AA) has been estimated to exhibit antiatherosclerotic effects, but the mechanism remains unclear. This study aimed to identify the role of AA in oxidized low-density lipoprotein (ox-LDL)-induced vascular smooth muscle cell (VSMC) behaviours and to explore the effects of microRNAs (miRNAs). Methods. A scratch wound-healing assay was used to detect the migration of VSMCs, and immunocytochemistry and western blotting for SM22ɑ were used to evaluate phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Several groups have reported that circRNA (for example, Hsa_circ_0031608) modulates the VSMC phenotype in intracranial aneurysms [ 51 ]. Furthermore, miRNAs, such as miR-103-3p or miR-128-5p, have been found to be related to VSMC function in vascular calcification or atherosclerosis [ 52 , 53 ]. Utilizing overexpression and rescue assays in combination with luciferase assays, our study depicted the regulative axis of circZXDC and miR-125a-3p in VSMC phenotype change under OGD conditions, which further provides more detailed information for MMD neointima.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported that circRNA (for example, Hsa_circ_0031608) modulates the VSMC phenotype in intracranial aneurysms [ 51 ]. Furthermore, miRNAs, such as miR-103-3p or miR-128-5p, have been found to be related to VSMC function in vascular calcification or atherosclerosis [ 52 , 53 ]. Utilizing overexpression and rescue assays in combination with luciferase assays, our study depicted the regulative axis of circZXDC and miR-125a-3p in VSMC phenotype change under OGD conditions, which further provides more detailed information for MMD neointima.…”
Section: Discussionmentioning
confidence: 99%